Ketahanan Lapang Empat Aksesi Kelapa Genjah Kopyor Terhadap Hama Oryctes rhinoceros di Kabupaten Pati, Jawa Tengah - MELDY L.A. HOSANG (Buletin Palma, 2010)
Field Resistance of four kopyor dwarf coconut Accessions to Oryctes rhinoceros in Pati District, Central JavaThe objective of this research was to determine the level of field resistance of four kopyor dwarf coconut accessions to . The research was conducted on farmers' land having kopyor dwarf coconut palms in Pati, Central Java in April 2010. Three districts were observed and 60 kopyor dwarf coconut accession from each sub district were randomly selected and observed. Observations were recorded by counting the total number of frond cuts on five fully opened young fronds. Results showed that the highest number of frond cuts of dwarf coconut accessions were found on green accession (GKH), followed by brown (GKC), Yelow (GKK) and the least number was found on Orange accession (GKG) with average number of cuts/frond was 0,57, 0,42, 0,22 and 0,13 respectively. The estimation of the reduction of coconut production showed that the highest reduction around 20% was found on GKH and the lowest one on GKG which is less than 10%.